1995
DOI: 10.1002/j.1460-2075.1995.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of porcine pancreatic phospholipase A2.

Abstract: The lipolytic enzyme phospholipase A2 (PLA2) is involved in the degradation of high‐molecular weight phospholipid aggregates in vivo. The enzyme has very high catalytic activities on aggregated substrates compared with monomeric substrates, a phenomenon called interfacial activation. Crystal structures of PLA2s in the absence and presence of inhibitors are identical, from which it has been concluded that enzymatic conformational changes do not play a role in the mechanism of interfacial activation. The high‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 48 publications
2
34
2
Order By: Relevance
“…A nitrogen atom of His 64 , which may act as a general base-catalyst, is 5.5 Å apart from the calcium(II) ion. Similar alignments of imidazole and carboxylate groups are well known in the active center of the other calcium-dependent PLA 2 s, such as porcine pancreatic PLA 2 (12).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…A nitrogen atom of His 64 , which may act as a general base-catalyst, is 5.5 Å apart from the calcium(II) ion. Similar alignments of imidazole and carboxylate groups are well known in the active center of the other calcium-dependent PLA 2 s, such as porcine pancreatic PLA 2 (12).…”
Section: Resultssupporting
confidence: 60%
“…Several structural studies of PLA 2 in solution (12) and in crystal (13)(14)(15)(16)(17)(18)(19)(20) have been reported. The crystal structural studies of secreted PLA 2 s have shown that the overall structures of class I PLA 2 s are similar to those of class II enzymes.…”
mentioning
confidence: 99%
“…The formation of a hydrogenbonding network extended from the catalytic site is incomplete when compared with the crystal structure (11). However, the solution structure of the porcine PLA 2 complexed with a competitive inhibitor and micelles showed that the N-terminal region and surface loop take stable conformations and form the complete hydrogen-bonding network, as seen in the crystal structure (12).…”
Section: Quality Of the Electron Density Map And The Current Model-asmentioning
confidence: 97%
“…However, the catalytic hydrogen-bonding network and the substrate-binding site are flexible in the calcium-bound form of the bacterial PLA 2 . Interestingly, recent studies of eukaryotic PLA 2 s using the NMR method (11)(12)(13) showed the flexible feature of the enzyme at a part of catalytic hydrogen-bonding network and the substrate-binding site. The flexibility in the crystal structure of the calcium-bound S. violaceoruber PLA 2 may be associated with these observations in the solution structures of eukaryotic PLA 2 s.…”
Section: Quality Of the Electron Density Map And The Current Model-asmentioning
confidence: 99%
See 1 more Smart Citation